The blighted youth: The impact of recessions and policies on life-cycle unemployment - Bernabe Lopez-Martin; Naoki Takayama (Banco de México, 2015)
We construct a theoretical model of labor markets with human capital accumulation to understand and quantify the earnings losses for young workers generated by unemployment: unemployment represents time forgone in terms of human capital accumulation, which adversely affects long-term income prospects of individuals. We show that lifetime earnings losses generated by job displacement are larger for individuals with lower capacity to accumulate human capital and during an economic downturn, as documented in the empirical literature. At the aggregate level, the framework delivers youth unemployment rates that are higher and more sensitive to fluctuations in aggregate productivity than total unemployment rates. Additionally, in economies with a higher tax-wedge, unemployment rates are more sensitive to aggregate productivity shocks. A higher tax-wedge and minimum wage increase the long-term earnings losses produced by job-displacement, especially for low-skill individuals.
Keywords: E24; E32; J63; J64; 330; aggregate fluctuations; directed search; unemployment; worker heterogeneity; life cycle; human capital